MULTIMODAL DISCOURSE ANALYSIS OF IMPLICATURES IN DETECTIVE CONAN COMIC SERIES 1 - Aisyah Nabilah Chamsyah; Naylus Syafa’ah; Shany Eva Dewi (Perkumpulan Madani Publisher Indonesia, 2025)
Comics are not only a medium for visual storytelling, but also rich in implicit meanings communicated through multimodal cues. This research explores how implicatures - unstated but implied meanings - are constructed through the visual expressions of the main characters in Detective Conan Volume 1. Using the Multimodal Discourse Analysis (MMDA) framework, this study investigates the interaction of semiotic modes such as gestures, gaze direction, facial expressions, and panel layout in selected scenes. Ten scenes were purposively selected based on the density of non-verbal cues and their narrative importance. A qualitative-descriptive method was used to analyze how these multimodal elements contribute to the construction of implicit meaning. The findings reveal that non-verbal modes often carry equal or greater communicative weight than verbal texts, especially in revealing characters' emotions and intentions. Visual cues-such as narrowed eyes or directed gaze-are often pragmatic indicators that invite readers to interpret meanings beyond what is explicitly stated. This study confirms the value of comics as authentic multimodal texts for pragmatic analysis. This research shows that comics can be an effective teaching tool in language or pragmatics classes. The integration of multiple modes in comics allows readers to capture meanings that are not directly stated, but implied through multimodal contexts.